2022
DOI: 10.1186/s12890-022-02291-6
|View full text |Cite
|
Sign up to set email alerts
|

The role of platelet-related parameters for the prediction of NAFLD in OSAHS patients

Abstract: Purpose As the detection of non-alcoholic fatty liver disease (NAFLD) is imperative for the prevention of its complications, we aimed to explore the predictive value of platelet to lymphocyte count ratio (PLR) and white blood cell count to mean platelet volume ratio (WBC/MPV) in relation to the occurrence of NAFLD among patients with obstructive sleep apnea–hypopnea syndrome (OSAHS). Methods This was a cross-sectional study consisting of 351 patie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
6
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(8 citation statements)
references
References 45 publications
2
6
0
Order By: Relevance
“…Several studies have shown conflicting results on platelet-related parameters and NAFLD. Previously, Chen et al revealed that PLR and WBC/MPV were closely related to the occurrence of NAFLD among obstructive sleep apnea–hypopnea syndrome patients, and in the subgroup analysis, WBC/MPV and PLR had good performance in NAFLD prediction in the subgroup with BMI < 28 kg/m 2 , but not in BMI ≥ 28 kg/m 2 21 . However, Duan et al showed that platelet-related parameters such as PLR and MPV are not associated with NAFLD in obese children, but inflammatory cytokines such as IL-1β, IL-6, and IL-17 levels were significantly associated with NAFLD 22 .…”
Section: Discussionmentioning
confidence: 87%
See 2 more Smart Citations
“…Several studies have shown conflicting results on platelet-related parameters and NAFLD. Previously, Chen et al revealed that PLR and WBC/MPV were closely related to the occurrence of NAFLD among obstructive sleep apnea–hypopnea syndrome patients, and in the subgroup analysis, WBC/MPV and PLR had good performance in NAFLD prediction in the subgroup with BMI < 28 kg/m 2 , but not in BMI ≥ 28 kg/m 2 21 . However, Duan et al showed that platelet-related parameters such as PLR and MPV are not associated with NAFLD in obese children, but inflammatory cytokines such as IL-1β, IL-6, and IL-17 levels were significantly associated with NAFLD 22 .…”
Section: Discussionmentioning
confidence: 87%
“…Cut-off values that optimized both sensitivity and specificity were selected. One hundred iterations were performed to split the train-test set in a 7:3 ratio 19 , 21 . The results tailored to the new MASLD definition were also appended to the supplementary figures and tables.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…On the other hand, platelets can cause liver inflammation by enhancing the recruitment of white blood cells in the sinusoidal endothelium, and can further activate effector cells, thereby amplifying liver injury. Various long-term studies have shown that platelets induce the progression of NAFLD primarily by generating a pro-inflammatory and pro-fibrotic environment in the liver ( 51 , 52 ). In the presence of inflammatory diseases, circulating lymphocytes are often reduced ( 48 ).…”
Section: Discussionmentioning
confidence: 99%
“…Regarding PLR, several studies similarly suggested that PLR may be more useful as a marker in determining the increased thrombotic state and inflammatory response in morbid obesity, obstructive sleep apnea–hypopnea syndrome, overall survival in patients with NAFLD-related hepatocellular carcinoma 5 , 36 , 41 , 42 . Taken together, it seems that PLR has relatively higher diagnostic accuracy for liver fibrosis 35 .…”
Section: Discussionmentioning
confidence: 99%